2021
DOI: 10.28940/terra.v39i0.796
|View full text |Cite
|
Sign up to set email alerts
|

Respuesta agronómica de dos variedades de tomate (Solanum lycopersicum L.) a la aplicación del bioestimulante con quitosano

Abstract: El quitosano tiene propiedades promotoras del crecimiento y la nutrición de los cultivos. Es un bioestimulante que en estudios previos demostró su actividad sobre la regulación del crecimiento, promoción de la germinación y el vigor de las plantas e incremento del rendimiento agrícola. En el presente trabajo se evaluó el efecto individual o combinado de la aplicación de quitosano por imbibición de semilla y vía foliar al inicio de floración sobre la respuesta agronómica (crecimiento, desarrollo y rendimiento) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
1
2
0
2
Order By: Relevance
“…in the nursery phase, so that the dose of 500 mg of chitosan per liter of water improved the survival conditions of the seedlings, observing a possible negative effect when increasing the dose up to 1000 mg of chitosan per liter of water. This agrees with (Rivas-García et al, 2021;Reyes-Perez et al, 2022), who, at the tomato and cocoa nursery level, maintains that the application of 3000 mg L -1 and 1000 mg L -1 doses respectively of foliar Quitosan based products (Quitomax®) should be considered as one of the most important to guarantee success in obtaining seedlings, since that a higher dose could generate negative effects, as well as economic losses due to a waste of inputs.…”
Section: Discussionsupporting
confidence: 84%
“…in the nursery phase, so that the dose of 500 mg of chitosan per liter of water improved the survival conditions of the seedlings, observing a possible negative effect when increasing the dose up to 1000 mg of chitosan per liter of water. This agrees with (Rivas-García et al, 2021;Reyes-Perez et al, 2022), who, at the tomato and cocoa nursery level, maintains that the application of 3000 mg L -1 and 1000 mg L -1 doses respectively of foliar Quitosan based products (Quitomax®) should be considered as one of the most important to guarantee success in obtaining seedlings, since that a higher dose could generate negative effects, as well as economic losses due to a waste of inputs.…”
Section: Discussionsupporting
confidence: 84%
“…An increase in the fresh biomass of tomato fruit and root was reported in response to the application of chitosan (Chanaluisa-Saltos et al, 2022;Rivas-García et al, 2021). The diameter of the broccoli head variety italica, also increased in response to chitosan (Yildirim et al, 2011), in contrast, Kałużewicz et al (2018) found no effect on this variable in response to the application of an amino acid as a biostimulant in broccoli of the variety Tiburon.…”
Section: Resultsmentioning
confidence: 94%
“…Likewise, López et al, 57 obtained higher growth and production in tomatoes treated with chitosan at a concentration of 300mg/L compared to tomatoes without chitosan, because chitosan increases the chlorophyll content in the leaves. While Rivas-García et al, 73 in two tomato varieties increased yield. Reyes-Pérez et al, 68 with the application of chitosan at a dose of 2g/L-1 in two tomato varieties, increased the percentage of germination, growth and yield; because chitosan increases photosynthesis, chlorophyll synthesis induces stomatal closure for more efficient use of water, in addition, chitosan degradation generates ammonium, a source of plant nitrogen.…”
Section: Promotion Of Plant Growthmentioning
confidence: 88%